The influence of frequency of cutting on the yield, chemical composition, digestibility and nutritive value of some grass species - Louw, J. G (Stellenbosch : Stellenbosch University, 2012)
Reprinted from: The Onderstepoort Journal of Veterinary Science and Animal Industry, v. 2, no. 1, July 1938.